Effect of Chemical Disinfectants and Repair Materials on the Transverse Strength of Repaired Heat-Polymerized Acrylic Resin - Ayman E. Ellakwa, BDS, MSc, PhD;1 and Ali M. El-Sheikh, BDS, MSD, (Journal of Prosthodontics, 2006)
The purpose of this study was to evaluate both the effects of immersion in different chemical disinfectant solutions and the type of repair material on the transverse strength of repaired heat-polymerized acrylic resin